Efek Penambahan Enzim Xilanase Dengan Level Serat Pakan Berbeda Terhadap Penampilan Produksi Ayam Pedaging - Heli Tistiana; Osfar Sjofjan; Eko Widodo; Irfan H Djunaidi; M Halim Natsir (TERNAK TROPIKA Journal of Tropical Animal Production, 2018)
This study was conducted to determine the effect of addition of xylanase enzymes in the diet with different levels of crude fiber on broiler performance. Materials used in this study were 100 broiler finisher 21 days of age and  unsexed. The method using a completely randomized design (CRD) with 5 treatments and each treatment was repeated 4 times. The treatment given was to use different levels of bran then be added as much as 0.01% xylanase enzyme for each kilogram of bran. Statistical analysis showed that the addition of xylanase in the feed with different levels of fiber to give a different effect was not significant (P> 0.05) on feed consumption, body weight gain, feed conversion, carcass weight and fat percentage. The conclusion of this study is the addition of xylanase in feed that has different levels of bran have a positive influence on the performance of broiler production which include feed intake, body weight gain, feed conversion, carcass weight percentage, and the percentage of abdominal fat. The best results were found in the use of T3,  the addition of 0.01% xylanase enzyme in the rice bran as much as 18% of total ration. It is recommended for use in combination with the feed additive xylanase early so allow time for the Adaptation of livestock in the metabolism of the body.